Influencia de los movimientos funcionales esforzados en los pacientes con escoliosis que acuden al Hospital Básico Dr. Nicolás Coto Infante, Cantón Vinces, Provincia Los Ríos, segundo semestre 2018. - Arévalo Velásquez, Byron Jesús (2018)
Scoliosis is a health problem in the spine since it causes a curvature to occur that affects the normal development of the patient. The investigation is carried out with the purpose of determining the influence of functional movements in scoliosis patients attending the Basic Hospital Dr. Nicolás Coto Infante, canton Vinces, Los Ríos province, second semester 2018, which will allow to reach a better knowledge about patients in order to achieve the establishment of alternatives that entail having alternative measures. The use of the inductive - deductive method has been considered, applying a field, bibliographic, descriptive, correlational and exploratory investigation, with the survey as a data collection technique, in the population of 70 patients that go to the Hospital, where they had to Most of them are between 19 and 45 years old, most of them have a basic educational level, which makes it difficult for them to have a normal life due to the pain that scoliosis causes. There was a Cronbach's alpha of 0.906 which shows a correlation very high, the Pearson's r was 0.837 **, which indicates that the correlation is direct and significant at the 0.01 level, the Student's t test showed that the working hypothesis was accepted, as conclusions were made that the patients They have ages of active work activity, the treatment is differentiated for each patient according to the need.